RNA m7G methylation regulators and targets significantly contribute to chronic obstructive pulmonary disease - Chenyu Zhu; Luyi Tan; Xinyu Zhang; Wenli Cheng; Min Li; Yibo Chen; Wenjuan Zhang (Scientific Reports)
Abstract Chronic obstructive pulmonary disease (COPD) is one of the most common lung injury diseases, closely associated with aging, air pollution and smoking exposure. The novel epigenetic modification 7-methylguanosine (m7G) RNA methylation affects the pathogenesis and progression of COPD. In this study, the combined roles of m7G methylation regulators were explored in COPD for the first time by integrated bioinformatic methods. The machine algorithms screened 7 disease signature genes relevant to clinical indicators, including CYFIP2, EIF3D, EIF4G3, GEMIN5, METTL1, SNUPN and NCBP2, and METTL1 was related to the progression in COPD. COPD patients could be well divided into two m7G subtypes by consensus clustering, and the two groups had differential immune profiles, visualized by single-cell sequencing and immune infiltration landscapes. More importantly, CAT was found to be a meaningful key target gene in METTL1-CAT axis for m7G methylation in COPD. We also used the cell premature senescence model for the preliminary validation of the above biosignature analysis results. The qRT-PCR and GSEA results revealed the important regulatory roles of the seven disease signature genes in COPD and aging-related diseases. Taken together, METTL1 and its target CAT have played an important role in COPD, as excellent candidates for its prevention and intervention.